Case Report: Cytoreductive Surgery and HIPEC Associated With Liver Electrochemotherapy in a Cholangiocarcinoma Patient With Peritoneal Carcinomatosis and Liver Metastasis Case Report - Stefano, Mauro; Prosperi, Enrico; Fugazzola, Paola; Benini, Beatrice; Bisulli, Marcello; Coccolini, Federico; Mastronardi, Costantino; Palladino, Alessandro; Tomasoni, Matteo; Agnoletti, Vanni; Giampalma, Emanuela; Ansaloni, Luca (Frontiers in Surgery, 2021)
Cholangiocarcinoma (CCA) is the second most common primary tumor of the liver and the recurrence after hepatic resection (HR), the only curative therapy, is linked with a worse prognosis. Systemic chemotherapy (SC) and liver loco-regional treatments, like trans-arterial chemoembolization (TACE) or radio embolization (TARE), have been employed for the treatment of unresectable intrahepatic metastasis (IM) with benefit on overall survival (OS), but SC has a limited effect on peritoneal metastasis (PM). In the last years novel treatments like electrochemotherapy (ECT) with bleomycine (BLM) for IM and cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS & HIPEC) for PM have been applied in small series but with encouraging results. We hereby describe the first synchronous application of ECT and CRS & HIPEC for the treatment of a patient with IM and PM from CCA. A 47-year-old male patient with CCA underwent HR followed by adjuvant SC. After 14 months, for the occurrence of IM, the patient underwent a second HR and SC. Nonetheless a new recurrence occurred and a third attempt of HR was proposed. Due to the intraoperative finding of unresectable IM with PM, no resective procedure was performed and the patient was referred to our center. CRS & HIPEC with cisplatin and mythomicin for PM and ECT with BLM on a bulky metastasis of the hepatic hilum were performed after 38 months from the first HR. The length of hospital stay was 19 days. At the computed tomography (CT) performed 11 days after treatment complete necrosis of the treated IM was detected. CT scan after 3 and 6 months and magnetic resonance after 9 months were performed. Necrosis of the treated IM nor PM, but progression of the residual liver lesions was observed. After 3 months the patient received SC and underwent TACE after 8 months and TARE after 9 months for the residual liver metastases. At 14 months from CRS & HIPEC the patient is alive, in good condition and with stability of the disease. The association of ECT and CRS & HIPEC could be safe and effective for the treatment of unresectable recurrent intrahepatic CCA with PM.